(untitled) (Medico Legal Update, 2020)
Sensory evolution of walnut fruit sere testes by groups of assessors some lecturer in my department whom they have perfectly experience of this purpose. Acid value and Peroxidase value are tested to illustrate change in oiliness and changing in the taste, flavor, odor,texture and kernel color and to notice the differences among two storage condition in two different temperature (4°C, 25°C), in zero time after 18months of storage visual properties of kernel walnuts there were some properties evaluated in walnut (appearance of kernel, to assess its flavor, bitterness, astringency, texture, crispness and oiliness. Visual appearance of Kernel of walnuts was evaluated similarly by both groups of assessors. However, each group of assessors had quite different perceptions for tasting internal traits of the kernels. In the present study useful data of sensory characteristics of walnut fruits were obtained.